ASSOCIATION BETWEEN FAMILY INCOME, SUBCLINICAL MYOCARDIAL INJURY, AND CARDIOVASCULAR MORTALITY IN THE GENERAL POPULATION - Sneha Chebrolu, MD (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD Risk Factors Background: Both low family income and subclinical myocardial injury (SCMI) are risk factors for cardiovascular disease (CVD) mortality. However, the impact of their joint association on CVD mortality is unclear. Therefore, we sought to examine the joint associations of family income and SCMI with CVD mortality. Methods: This analysis from the third National Health and Nutrition Examination Survey (NHANES-III) included 6,805 participants (age 59.1±13.4 years, 52.3% women, and 49.8% White) free of CVD at baseline. Family income was assessed using the poverty-to-income ratio (PIR) and categorized into low (PIR<1), middle (PIR=1-4), and high (PIR>4) income. A validated ECG-based cardiac infarction injury score (CIIS) ≥10 was considered positive for SCMI. CVD mortality was determined using the National Death Index. Cox-proportional hazard analysis was used to evaluate the associations of family income and SCMI, separately and jointly, with CVD mortality. Results: A total of 1,782 individuals (26.2%) had SCMI at baseline. During a median follow-up of 18.2 years, 856 (12.6%) events of CVD mortality occurred. In separate multivariable Cox models, SCMI (vs. no SCMI) and middle- and low-income (vs. high-income) were each associated with a higher risk of CVD mortality [HR(95%CI): 1.34(1.16-1.54), 1.44(1.16-1.78), and 1.59(1.22-2.07), respectively]. Compared to high-income participants without SCMI, those with low-income and SCMI had the highest risk of CVD mortality (Table). Conclusions: Lower family income and SCMI are associated with CVD mortality, and their concomitant presence is associated with the highest risk. Family income and SCMI may help in the individualized assessment of CVD risk.